1982
DOI: 10.1126/science.6123151
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Fibers to Limulus Eyes Synthesize and Release Octopamine

Abstract: Octopamine synthesized in vitro from tyramine by Limulus lateral and ventral eyes was located by light microscopic and electron microscopic autoradiography in efferent fibers which innervate ventral photoreceptors and lateral eye ommatidia. Newly synthesized octopamine was released from efferent fibers in response to depolarization in high concentrations of potassium. We propose that octopamine is a neurotransmitter of efferent fibers that may modulate basic retinal processes such as photoreceptor sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…Neither rhabdom turnover nor its control mechanisms have been studied in ventral photoreceptors. Likewise, no one has yet been able to demonstrate efferent suppression of spontaneous potential fluctuations in dark-adapted ventral photoreceptors, The central thrust of our study and that of Stern et al (1982), coupled with the findings of Battelle et al (1982) that efferent fibers in the ventral eye synthesize and release octopamine, suggest that this preparation may be very useful for the study of efferent function and basic phototransduction, in a system simpler than the lateral eye, but one that is still structurally and functionally well organized.…”
Section: Efferent Innervation Of the R Lobementioning
confidence: 77%
See 2 more Smart Citations
“…Neither rhabdom turnover nor its control mechanisms have been studied in ventral photoreceptors. Likewise, no one has yet been able to demonstrate efferent suppression of spontaneous potential fluctuations in dark-adapted ventral photoreceptors, The central thrust of our study and that of Stern et al (1982), coupled with the findings of Battelle et al (1982) that efferent fibers in the ventral eye synthesize and release octopamine, suggest that this preparation may be very useful for the study of efferent function and basic phototransduction, in a system simpler than the lateral eye, but one that is still structurally and functionally well organized.…”
Section: Efferent Innervation Of the R Lobementioning
confidence: 77%
“…The results of studies of efferent morphology using labeled efferents and autoradiography have been reported separately (Battelle and Chamberlain, 1980;Battelle et al, 1982;. Our examination of normal tissue revealed that efferent fibers have relatively lucent cytoplasm, and contain mitochondria, filaments, and two types of vesicles--small, lucent circular profiles (Fig.…”
Section: Ultrastructure Of Other Elements: Glia and Efferent Fibersmentioning
confidence: 90%
See 1 more Smart Citation
“…These clock-driven efferent neurons innervate all cell types in LEs (Fahrenbach, 1975;Fahrenbach, 1981), and release the biogenic amine octopamine (OA) from their axon terminals (Batelle et al, 1982;Battelle and Evans, 1984;Evans et al, 1983). OA stimulates a rise in cAMP in Limulus photoreceptors (Kaupp et al, 1982) and LE slices (Dalal and Battelle, 2010), and many of the known effects of clock input to LEs are mimicked by OA and other treatments that activate the cAMP cascade (reviewed in Battelle, 2002;Dalal and Battelle, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are driven by signals from an internal circadian clock and amplified by light. The effect of the clock can be mimicked by octopamine, the neurotransmitter released from the clock-driven efferent neurons that innervate the pigment cells, and activation of a cAMP cascade (Battelle et al, 1982;Battelle and Evans, 1984;Battelle, 2002;Dalal and Battelle, 2010). The receptor responsible for the effect of light is unknown.…”
Section: Research Articlementioning
confidence: 99%